Gender and Authority in Caryl Churchill’s Vinegar Tom (1976) - Rgwan Abdalhameed Shuash , Researcher; Rana Ali Mhoodar, Rese. (lark, 2023)
This article gives a feminist examination of Caryl Churchill’s Vinegar Tom (1976). This play is in reality, Churchill’s feminist lens through which the playwright offers an account of interactions of gender and authority via the 17th-century witchcraft trials in England from a distinctly feminist standpoint. It is – as a research article – a freshly developed consideration of that age that might build a different sort of history to the authorized male-made. In a significant way, part from this article, is to assess Churchill’s in terms of form and substance. The dramatist personifies revolutionary ideas presented in a fresh and original way. She majorly concentrates on the female-subjective status via her dramatic depiction and also builds a new women’s portrayal through the eyes of women instead of men. Janelle Reinelt (1989)’s feminist theory and the problem of performance is adopted to set a focus on two major concepts, namely gender and class. The subject of Vinegar Tom deals with extremely sensitive themes such, subjugation of women within a masculine society, rights, gender formation, women identity and sexual orientations. Such controversial issues are depicted via the employment of several inventive instruments and approaches. The majority of Churchill’s use of theatrical elements consists of doubling, monologues, music, and songs. Taking everything into consideration, this article searches in Churchill’s Vinegar Tom dramatically, theatrically, and historically. Using a variety of theatrical approaches to historical reconstruction, it portrays Churchill as a self-identified socialist feminist.